Noncompliance of the occupational safety and health legislation in the Malaysian construction industry - Abdul Rahim, A. H.; A. R. A., Razak; A. M., Yusof; Putra Jaya, Ramadhansyah; R., Zakaria; Eeydzah, Aminudin; M. A. S. K., Anuar; Khairulzan, Yahya; Zaiton, Haron; R., Yunus; I. A., Rashid (IOP Publishing, 2019)
Occupational Safety and Health Act 1994 (OSHA 1994) is a tool for the employer, employee and manufacturer to put efforts in securing safety, health and welfare at work place. But, the increase in prosecution cases under OSH legislation indicates the lack of compliance to the regulations. A prosecution can be translated as one of the frequently employed instruments for the enforcement of health and safety legislation. The objective of this study is to analyze the most common non-compliance cases of OSH legislative provision from 2005 until October 2017 compiled by the Department Occupational Safety and Health (DOSH). The data of the cases were analyzed using frequency distribution analysis and content analysis. The result of the study shows that the most non-compliance with OSH legislation in Malaysia relates to the general duties of employers and self-employed persons to their employees (Section 15(1)). The second most common non-compliance of OSHA is section 17 regarding employer's failure to provide safe work system. The third and fourth most common non-compliance of OSHA is section 32 and 29 regarding the employer's failure to report the accidents and the employer's failure to provide competent safety and health officer. To increase compliance to legislation, full top management commitment, active worker engagement and effective safety and health committee are amongst top preferred solutions.